Coordinated fibre and wireless spectrum allocation in SDN-controlled wireless-optical-cloud converged architecture - Ruffini, Marco (My University, 2019)
We provide an experimental demonstration of LTE multi-cell resource allocation in a converged LTE-over-PON architecture. Our SDN controller dynamically adjusts the wireless bandwidth of each cell, according to their demand, jointly with their fronthaul rate and reserved PON capacity.
European Conference on Optical Communications (ECOC)
PUBLISHED
Keywords: Cloud Radio Access Network (C-RAN); Coordinated Multi Point transmission and reception (CoMP); Enhanced Inter-Cell Interference Coordination (eICIC); Multi-cell packet scheduling